The Role of Political Behavior in the Relationship between Managerial Intelligence and Entrepreneurial Success - Taha , Mr. Azad H.; Khader, Dr. Shihab A.; Ali, Mr. Fakhraldin B. (Mitanni Journal of Humanitarian Sciences, 2023)
This piece of work aims at identifying the role of political behavior in the relationship between managerial intelligence and entrepreneurial success among the managerial leaders at Duhok Technical University and Erbil Technical University in the Kurdistan Region - Iraq. This research provides theoretical milestones about the three variables, as well as apply them in practice through the design of the questionnaire form and its distribution to collect information from the managerial leaders in the two research samples. There are 122 valid statistical analysis forms on SPSS program. This piece of research tries to find the answer to the following question: Is there a role for political behavior in the relationship between managerial intelligence and entrepreneurial success among the managerial leaders in Dohuk Technical University and Erbil Technical University? The research’s main hypothesis was marked with the existence of the role of political behavior in the relationship between managerial intelligence and entrepreneurial success among the managerial leaders in Dohuk Technical University and Erbil Technical University. The research reaches to a set of conclusions, the most important of which is the negative role of political behavior in the relationship between managerial intelligence and the entrepreneurial success of the managerial leaders at Dohuk Technical University and Erbil Technical University.